“Sob cuidados médicos”: homossexualidade masculina nos prontuários do Pinel (1920-1940) - Silva, Redson dos Santos (2016)
Having as central focus of analyze cases of hospitalized homosexuals in Pinel (Pirituba/SP) under diagnose of sexual reversal in 1920 to 1940. This research tries to understand the representation and differentiating factors wrought to medical discourse and criminologist about practise and homosexual body, classifying them, indicating standards of conduct and deny them of a freedom in their sexual lives. The medical and criminal sources checked can be found in the public archives of State. They are patients records, some cases od hospital admission in Pinel Sanatorium. They were researched in detailed way and revealed the expressions and contexts of that time, however still introduce continuity contemporaneity. The criminal law came from european theory circulated and inspered the brazilians interpretations in this period of time. In spotlight we have some interpretations done by Cesar and Lombroso about fhysical of the criminal person. In 1920, from that date increased in relevance thelegal medicine. The change of the focus in order to achieve the notion of homeland cleaning emphasizing the privilege in a pedagogical behaviour into their citizens. The homosexuality was faced as deviating in your biological and ethical aspects. Without to highlight the religian speech which controled and effected several questions of moral order. Representing the homosexuality as a grave sin of sodomia. The new context increased the interpretations came up with professionals of the medicine that started up to find explanations to the homosexuality, a behaviour considered deviating, abnormal, degrading in social meaning, following this conceptions; the homosexuality was disease, consequently looked for treatments aiming the heal. Primarily, they prioritized the biological causes before of disease to be discussed what the more efficient treatment to heal the homosexuals. Some of this could besince confinament to reeducation or push the carater as issue to being sort out. (Pinel was a institution among others with the only aim is heal this kind of disease). Including injections of insulin, electrical shockes